Peningkatan Kemampuan Berpikir Kritis dalam Pemecahan Masalah Matematis Menggunakan Pendekatan Open Ended - Kowiyah Kowiyah (Jurnal Inovasi Pendidikan Dasar, 2016)
This research aims to investigate the application of open ended approach, to increase students’ critical thinking ability in mathematic problem solving. This research was conducted at SD Islam Terpadu Al-Khairaat Jakarta Timur, with 25 students as subject of the research. This is an action research using Kemmis and McTaggart’s model in two cycles. Each of the cycles consists of planning, acting, observing and reflecting. The result shows the increase of students’ critical thinking ability in mathematic problem solving, by means of open ended approach. It was proved with the increase of students’ grade from 63.92% in the first cycle to 73.80% in the second cycle. The activity of teacher and student using open ended approach achieves mastery learning (100%) at the end of the cycle.